Pengetahuan Ibu tentang Metode KB dengan Pemilihan Metode Kontrasepsi - Deasy Christania Embong Bulan; Nelfa Takahepis; Zainar Kasim (Jurnal Riset Ilmu Kesehatan Umum dan Farmasi (JRIKUF), 2025)
The selection of contraceptive methods is an important part of family planning and reproductive health. However, if the selection of contraceptive methods does not align with the individual's physical condition and health, it can lead to various detrimental health impacts, including hormonal side effects, infections and irritations, ectopic pregnancies, allergic reactions, perforation and dislocation of contraceptive devices, and psychological disturbances. The objective of this study is to determine the relationship between mothers' knowledge of contraceptive methods and the selection of contraceptive methods in the Working Area of Wawonasa Health Center. The research uses a cross-sectional design. The sample in this study consisted of 57 respondents using purposive sampling technique. Data collection on knowledge and the selection of contraceptive methods was conducted using a questionnaire, and analyzed using the chi-square statistical test. The research results show that the majority of respondents are aged 19-40 years, totaling 47 respondents (82.5%). The most common occupation is unemployed/housewife, totaling 41 respondents (71.9%). The most common education level is high school, totaling 29 respondents (50.9%). the most common knowledge category was the "poor" category, with 44 respondents (77.2%), and the most common contraceptive method was the hormonal contraceptive method, with 30 respondents (55.6%). The results of the chi-square test showed a p-value of 0.001, which is < α 0.05. Conclusion: There is a relationship between mothers' knowledge of contraceptive methods and the choice of contraceptive methods in the working area of Wawonasa Health Center. It is recommended that respondents be given more access to education so they can make better decisions regarding contraception